PERSEPSI MASYARAKAT BLAJUD KARDULUK TENTANG MODERNISASI PESANTREN TRADISIONAL - Abd. Qadir; Syurayyah Hijrin (Reflektika, 2019)
Pesantren is an Islamic educational institution that has its own characteristics and is different from other educational institutions. Islamic boarding schools are the oldest and original Islamic educational institutions in Indonesia which can display a system that is well known for traditional and Islamic boarding schools can be interesting to study and research. Islamic boarding schools have a major influence on people's lives, especially because they grow and develop from and for the community itself. However, with the development of the times, pesantren have gradually responded to various social changes that have occurred by changing according to the needs of the community so that pesantren have experienced a shift from the effects of modernization. Likewise with the An-Najah Karduluk Islamic boarding school which carried out modernization. By using a qualitative case study approach. To find out how the Blajud Karduluk community perceives the modernization of traditional Islamic boarding schools at the An-Najah Islamic Boarding School which is described in two research focuses, namely: 1. What are the perceptions of the Blajud Karduluk community regarding the modernization of traditional Islamic boarding schools, a case study of An-Najah Islamic Boarding School 2. What are the forms of modernization efforts An-Najah traditional Islamic boarding school. The results of the analysis found that the perceptions of the Blajud Karduluk community regarding the modernization of traditional pesantren at An-Najah Islamic boarding school were getting good perceptions because of the support from the surrounding pesantren community by changing the salaf system to a modern system (formal education). In addition, there are forms of efforts to modernize the traditional pesantren itself, there are formal schools, namely PAUD, RA, MI, MTs, & MA and extracurricular activities that hone the brain abilities and skills of students, namely drumband, scouts, computer tutoring, 2 language courses (Bahasa English & Arabic) and so on with this is evidence of the reforms carried out by the pesantren.